2022
DOI: 10.7554/elife.83883
|View full text |Cite
|
Sign up to set email alerts
|

Urotensin II-related peptides, Urp1 and Urp2, control zebrafish spine morphology

Abstract: The spine provides structure and support to the body, yet how it develops its characteristic morphology as the organism grows is little understood. This is underscored by the commonality of conditions in which the spine curves abnormally such as scoliosis, kyphosis and lordosis. Understanding the origin of such spinal curves has been challenging in part due to the lack of appropriate animal models. Recently, zebrafish have emerged as promising tools with which to understand the origin of spinal curves. Using z… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 67 publications
0
19
0
4
Order By: Relevance
“…We found that 106 out of 614 upregulated genes were targets of Foxj1, among which 77 were direct targets (Supplementary Table 3). Several genes encoding regulators of embryonic axis curvature were also upregulated in rpgrip1l -/- fish, among which pkd1b (37), urp1 and urp2 (12,13,16) and sspo (5,10,11). Finally, GO terms enrichment analysis also highlighted processes associated with inflammation and innate and adaptive immune responses, as described for the scoliotic ptk7 model (19) sharing for example irg1l and complement genes up-regulation (Fig 5 C, E, and Supplementary fig 4A).…”
Section: Resultsmentioning
confidence: 99%
“…We found that 106 out of 614 upregulated genes were targets of Foxj1, among which 77 were direct targets (Supplementary Table 3). Several genes encoding regulators of embryonic axis curvature were also upregulated in rpgrip1l -/- fish, among which pkd1b (37), urp1 and urp2 (12,13,16) and sspo (5,10,11). Finally, GO terms enrichment analysis also highlighted processes associated with inflammation and innate and adaptive immune responses, as described for the scoliotic ptk7 model (19) sharing for example irg1l and complement genes up-regulation (Fig 5 C, E, and Supplementary fig 4A).…”
Section: Resultsmentioning
confidence: 99%
“…In zebrafish, CSF-cNs are also involved in spine deformities reminiscent of AIS, which rely on the maintenance of a controlled expression level of Urp1 and Urp2, two neuropeptides expressed from the embryonic life to adulthood in these sensory neurons 33 . Indeed, urp1;urp2 double mutants were recently reported to develop AIS-like phenotypes is zebrafish 51 , 52 . Moreover, a downregulation of Urp1/2 peptides expression level was reported in AIS mutant models with defective Reissner fiber acting upstream of CSF-cNs 18 , 19 .…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 3A, the vertebrae were generally curved, but there were no significant changes in the shape of the neural or haemal arches. To assess the deformity of individual vertebrae causing the curvature, the size of individual vertebrae was measured and expressed as the ratio of anterior/posterior height (H1/H2) and dorsal/ventral length (L1/L2) (Bearce et al, 2022). Figure 4 shows data for the 8th to 13th vertebrae of 5 individual fish.…”
Section: Detailed Observation Of Vertebra Shape By Ctmentioning
confidence: 99%